The Effect of Speaking Strategies on Iraqi EFL College Students (Journal of the College of Education for Women, 2019)
The present study deals with the effect of teaching speaking Strategies (SS) onEFL Iraqi College students. The use of speaking strategies not only solves learners’communication problems, but also enhances the learner’s interaction in target language,and improves their oral proficiency .The aim of the study is to find out the effect ofteaching SS used by EFL College students .The learner of the first stage is population ofthe study at the Department of English, College of Education /Ibn-Rushd .The sampleconsists of (60) students distributed on experimental group(A) as well as controlgroup(B) each group contains (30) students . In order to achieve the aim of the study,questionnaire has been constructed to be taught on the experimental group and a test.The questionnaire and the test have covered reduction strategies, achievement strategies,modified- interaction strategies and social-interaction strategies (table 1).The face validityof the test is proved by exposing it to a jury of specialists. For reliability, AlphaCronbach reliability coefficient has been used. The results indicate that the SS strategiesare useful in improving the students' conversation. Accordingly, recommendation andsuggestions for further studies are put forward.